2022
DOI: 10.3390/horticulturae8100883
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Garden Roses to Improve the Ecosystem Services They Provide

Abstract: With pronounced morphological and phenological diversity, garden roses have always been part of urban plantings. The significance of roses in ornamental and utilitarian (edible) horticulture can significantly be amended with novel ecosystem services, by shifting their breeding targets towards more than aesthetic and nutritional value. Thus the aim of this paper was to investigate the possibilities of newly bred (within the past decade) garden roses from the ‘Mella’ series as a possible ornamental, disease tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Firstly, many annuals were initially bred to provide long-term color aesthetics and not to attract pollinators, so some may possess little or no foraging resources (pollen or nectar) for flower-visiting insects, even though they have the benefit of being some of the easiest plants to grow [62]. For example, "double" flowers, or varieties of flowers with extra petals such as zinnia "Double Zahara", are often highly bred for human aesthetic appeal and are not accessible to pollinators [63,64]. Because annuals are often preferred for their ornamental value, their addition within gardens should be carefully balanced against more rewarding plants to provide foraging resources for bees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, many annuals were initially bred to provide long-term color aesthetics and not to attract pollinators, so some may possess little or no foraging resources (pollen or nectar) for flower-visiting insects, even though they have the benefit of being some of the easiest plants to grow [62]. For example, "double" flowers, or varieties of flowers with extra petals such as zinnia "Double Zahara", are often highly bred for human aesthetic appeal and are not accessible to pollinators [63,64]. Because annuals are often preferred for their ornamental value, their addition within gardens should be carefully balanced against more rewarding plants to provide foraging resources for bees.…”
Section: Discussionmentioning
confidence: 99%
“…Insect pollinators are attracted to plants by many interacting floral traits [45,60,63]. Recently, it was shown that the traits that most reliably influenced pollinator attraction are flower color, display area, and morphology, which coincidently are also the same traits usually selected for in the development of plant cultivars [86].…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al [112] investigated the yield, susceptibility to Botrytis cinerea and levels of antioxidants of 12 edible garden rose cultivars, concluding that the cultivars 'English Sachet', 'Eterna', 'San Francisco' and 'Maxim' exhibited the lowest sensitivity to disease. Rose material investigated by Božanić Tanjga et al [113] included seven garden rose cultivars from the 'Mella' series, bred by the private breeding company 'Pheno Geno Roses'. The results indicated the high potential of varieties from the 'Mella' collection for growing in urban conditions due to their attraction of a significant number of pollinators and their tolerance to the main diseasecausing agents.…”
Section: Urban Spaces' Designs With Fruit Species and Roses As Edible...mentioning
confidence: 99%
“…Roses, in general, are plants that thrive in light and heat, and they can completely reward the grower who provides appropriate conditions for the full expression of their biological and ornamental potential (Božanić Tanjga et al, 2022). Nevertheless, roses can thrive even in a world that is "imperfect" because they are extremely undemanding and adapt to various conditions.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%